Editorial - Osorio Guzmán, Maricela (2023)
This monographic issue, Mental Health at University, is the result of the work elaborated by a group of specialists from public and private Higher Education Institutions in Argentina, Brazil, Colombia, Spain, Mexico and Peru. They are works with different methodologies, but all of them underline the importance of retaking the student as an integral being, where not only the cognitive aspects traditionally emphasized in university education are highlighted, but also experiences of individual and social transformation, which entail the recognition of affective-emotional aspects; besides emphasizing the importance of designing curricular programs of studies that support, encourage and promote socioemotional learning.